Mössbauer Spectroscopy, Structural and Magnetic Studies of Zn2+ Substituted Magnesium Ferrite Nanomaterials Prepared by Sol-Gel Method. (13th August 2015) - He, Yun; Yang, Xingxing; Lin, Jinpei; Lin, Qing; Dong, Jianghui
Abstract : Zinc substituted magnesium ferrite nanomaterials M g 1 - x Z n x F e 2 O 4 (x = 0, 0.1, 0.3, 0.5, 0.7) powders have been prepared by a sol-gel autocombustion method. The lattice parameter increases with increase in Zn concentration, but average crystallite size tends to decrease by increasing the zinc content. SEM results indicate the distribution of grains and morphology of the samples. Some particles are agglomerated due to the presence of magnetic interactions among particles. Room temperature Mössbauer spectra of M g 1 - x Z n x F e 2 O 4 shows that the A Mössbauer absorption area decreases and the B Mössbauer absorption area increases with zinc concentration increasing. The change of the saturation magnetization can be explained with Néel's theory. It was confirmed that the transition from ferrimagnetic to superparamagnetic behaviour depends on increase in zinc concentration by Mössbauer spectra at room temperature. Saturation magnetization increases and coercivity decreases with Zn content increasing.